To be seen or not to be seen: Photovoice, queer and trans youth, and the dilemma of representation. Issue 4 (December 2015) - Holtby, Alix; Klein, Kate; Cook, Katie; Travers, Robb
Photovoice is increasingly lauded as one of a number of emergent research methodologies designed to be empowering for participants. In this paper, we explore the findings from a photovoice study with 15 queer and trans youth in a small urban centre in Ontario, Canada and some of the challenges faced in navigating photovoice ethics when working with a marginalized community that must grapple with dilemmas of visibility and representation in their daily lives. This paper identifies some practical considerations in confronting issues of representation in photovoice research, and reflects on the interaction of the research study with participants' ongoing negotiation of power imbalances in their daily lives.